Analisis Pola Perilaku dan Motivasi Bermain Judi Onilne Pada Mahasiswa di Era Digital - Ridha Al Munawar, Mumtaz Ali; Wiguna, Shandi; Insani, Alexa Putri Nur; Desyanti, Intan; Satrya, Muhamad Mario Darpa; Aldi, Muhammad; Rozak, Rama Wijaya Abdul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research contains the results of observations regarding the analysis of behavior patterns and motivations in playing online gambling on students in the digital era. In this age of technology, there are negative and om impacts. Of the many negative impacts arising from technological developments, the practice of online gambling is one of them. The rise of online gambling practices attacks not only parents, but also has an impact on students, especially students. This research was conducted with the aim of obtaining knowledge about the various factors that encourage students to practice online gambling, motivation, and behavior patterns caused by online gambling practices. This research uses descriptive qualitative methods conducted on 10 informants who are college students. The results of the research conducted show the emergence of consumptive behavior patterns, dependence, and addiction to online gambling. The phenomenon of online gambling also has risks for the perpetrators, such as decreased performance productivity, financial problems, mental health problems, and can trigger online gambling players to commit criminal acts. Then it is found that a person's motivation in practicing online gambling varies, including curiosity and economic needs.